Pengaruh Latar Belakang Pendidikan Terhadap Kompetensi Pegawai Di Biro Umum Sekretariat Daerah Provinsi Kalimantan Tengah - Elthara, Dellina; Jaya, Imanuel; Angela, Vivi Friskila (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
The purpose of this study is to identify whether educational background affects employee competence in the General Bureau of the Regional Secretariat of Central Kalimantan Province. This research uses associative quantitative research methods with a survey approach. Data collection was carried out through distributing questionnaires to 70 respondents selected based on education level using disproportionate stratified random sampling technique from a total population of 229 employees. The research findings show the influence of educational background on employee competence in the General Bureau of the Regional Secretariat of Central Kalimantan Province, as evidenced by the hypothesis test (t-test) with the results of 5.637 (t-count) > 1.99547 (t-table), which means that the null hypothesis (H0) is rejected, while the alternative hypothesis (Ha) is accepted. Furthermore, the acquisition of the correlation coefficient value is obtained at 0.424 (kendall's tau-b) and 0.537 (spearman rho) which indicates that the two variables studied are quite strongly and positively related. Then the acquisition of the coefficient of determination (R2) is 0.318 or equivalent to 31.8% which means that the Educational Background variable (X) has an influence contribution to the competency variable (Y) of 31.8%, while the remaining 68.2% is influenced by other variables outside the variables studied in this study. Keywords: Educational background, employee competence